2019
DOI: 10.1098/rspb.2018.2448
|View full text |Cite
|
Sign up to set email alerts
|

Conservation biology needs a microbial renaissance: a call for the consideration of host-associated microbiota in wildlife management practices

Abstract: The central aim of conservation biology is to understand and mitigate the effects of human activities on biodiversity. To successfully achieve this objective, researchers must take an interdisciplinary approach that fully considers the effects, both direct and indirect, of anthropogenic disturbances on wildlife physiology and health. A recent surge in research has revealed that host-associated microbiota—the archaeal, bacterial, fungal and viral communities residing on and inside organisms—profoundly influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
344
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(352 citation statements)
references
References 95 publications
(124 reference statements)
7
344
0
1
Order By: Relevance
“…A recent paradigm shift in biology has been the discovery of the breadth, diversity and importance of microbial communities associated with multicellular animals and plants. Termed the 'microbiome', these communities influence a number of traits associated with host health, physiology and development (Blaser, Bork, Fraser, Knight, & Wang, 2013;Gilbert, Jansson, & Knight, 2014), and as such have been the focus of attention in fields as diverse as human medicine and wildlife conservation (Kashyap, Chia, Nelson, Segal, & Elinav, 2017;Trevelline, Fontaine, Hartup, & Kohl, 2019). Host-microbiome systems are complex ecological communities encompassing an array of host-microbe and microbe-microbe interactions (Bauer, Kainz, Carmona-Gutierrez, & Madeo, 2018;Coyte, Schluter, & Foster, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent paradigm shift in biology has been the discovery of the breadth, diversity and importance of microbial communities associated with multicellular animals and plants. Termed the 'microbiome', these communities influence a number of traits associated with host health, physiology and development (Blaser, Bork, Fraser, Knight, & Wang, 2013;Gilbert, Jansson, & Knight, 2014), and as such have been the focus of attention in fields as diverse as human medicine and wildlife conservation (Kashyap, Chia, Nelson, Segal, & Elinav, 2017;Trevelline, Fontaine, Hartup, & Kohl, 2019). Host-microbiome systems are complex ecological communities encompassing an array of host-microbe and microbe-microbe interactions (Bauer, Kainz, Carmona-Gutierrez, & Madeo, 2018;Coyte, Schluter, & Foster, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many diseases (e.g., obesity, diabetes, and autistic disorder) are caused by specific gut microorganisms (Forslund et al, ; Kostic et al, ; Ley et al, ; Mulle, Sharp, & Cubells, ; Turnbaugh et al, ); therefore, a better understanding of the relationship between humans and the gut microbiome would be beneficial for human health and disease treatment. Beyond the application in the treatment of human disease, in recent years, some scientists have considered the application of the gut microbiome in the conservation of endangered animals (Bahrndorff, Alemu, Alemneh, & Lund Nielsen, ; Jiménez & Sommer, ; Redford, Segre, Salafsky, del Rio, & McAloose, ; Stumpf et al, ; Trevelline, Fontaine, Hartup, & Kohl, ; Wei et al, ; Yao, Xu, Lu, & Zhu, ). The scientists first propose the concept of conservation metagenomics, which is along with current methods, major scientific issues and significant implications in the study of host evolution, nutrition, physiology, and ecology and conservation (Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 41% of amphibian species are considered threatened, including 54·7% of the Urodela group commonly known as newts and salamanders (Hernandez, ). Despite a widely recognized need for microbiome research to be placed in a more ecological context – especially as it applies to wildlife conservation – few efforts have been made to integrate these fields, especially in a way that might actually address current management practices (Trevelline et al , ). The microbiota of amphibian skin is used as a defence mechanism against infections (Becker et al , ; Passos et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed that the microbiome of living animals can impact host health directly by influencing metabolism, development, inflammation or behaviour. However, the microbiome may also have an indirect influence on host health during interactions with infectious pathogens (Turnbaugh et al, 2006;Heijtz et al, 2011;Honda & Littman, 2012;Theis et al, 2013;Jani & Briggs, 2014). All amphibians show an important and diverse microbiota community on their permeable skin, which is thin and sensitive to their environment (Duellman & Trueb, 1986;Bataille et al, 2016).…”
Section: Introductionmentioning
confidence: 99%